STRATEGI PEMERINTAH PROVINSI RIAU DALAM ESPOR CPO (CRUDE PALM OIL) KE INDIA - Lulu Gusvica Irhandi; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Palm oil is one of the plantation products that becomes an export commodity and has a strategic role in the Indonesian economy, especially Riau Province. Riau Province is a province that has the largest area of palm oil and has the highest CPO (Crude Palm Oil) productivity in Indonesia, so that Riau Province exports CPO or palm oil. Export activities will generate income in the form of export value. This study describes the efforts of the Riau Province government in exporting CPO to India. The export of CPO commodities is one of the leading foreign exchange earnings for national exports. India is a destination country for Indonesian palm oil exports. The volume of Indonesian palm oil exports to India sometimes continues to increase every year. This research uses qualitative methods with data collection techniques through literature study sourced from several books, journals, official documents, articles, websites and interviews. This research uses the perspective of Neo-liberalism, the level of analysis of the nation state and the theory of international trade.. The results showed that the Riau Province government's strategy in exporting CPO to India included increasing the production and productivity of oil palm plantations optimally in Riau Province, which is competitive and has quality for plantation welfare; the realization of a sustainable bio-industrial farming system that produces a variety of healthy foods and high value-added products from agricultural biological resources; improve the human resources capacity of the apparatus/farmers to work professionally; improve the clean, transparent and thorough internal services of regional apparatus organizations in the plantation sector. Keywords: Strategy, Export, CPO, Cooperation